Reducing Free Riding Behaviour in Collaborative Work with Computer Supported Tools - Kloppenburg, Wieger; Nurlatifah, Eva; Spijkerboer, Christian; Yasmin, Fitri Almira (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
Free riding behaviour is a problem that has been around for many years. With all the new technological advances, there is much more collaborative work supported by online tools. These developments make it easier for individuals to become a free rider. This research carried out a literature study, to find the best method to reduce free-riding behaviour. Besides the methods, this study also elaborates some factors that trigger free riders in a group. The methods which are highlighted in this research are the implementation of assessments, group awareness tools, sufficient group size and enhancing team morale. However, the study found that none of the methods cover all the aspects of free-riding behaviour. It is suggested by this research to combine and improve various methods, to a new method that can effectively reduce free-riding behaviour in collaborative work with computer-supported tools.